A Robust Functional Genomics Approach to Identify Effector Genes Required for Thrips (Frankliniella occidentalis) Reproductive Performance on Tomato Leaf Discs - Abd-El-Haliem, Ahmed M.; Hoogstrate, Suzanne W.; Schuurink, Robert C. (Frontiers in Plant Science, 2018)
Thrips (Frankliniella occidentalis) is a persistent plant pest that is able to vector pathogenic viruses. Natural plant resistance to thrips has become a prominent breeding target in commercial crops. The main reason for this is the shift towards banning key pesticides used for controlling thrips infestations and the lack of effective alternatives. Despite this urgent need for crop plants that are resistant, or tolerant, to thrips infestation, the toolbox for studying genetic resistance to this insect is still underdeveloped. Essentially, there is a lack of robust protocols for the screening and identification of thrips genes relevant to its performance on crop plants. To bridge this gap, we have developed a functional analysis screening method. Our approach relies on the, Agrobacterium tumefaciens-mediated, homogeneous and transient ectopic expression of thrips genes in large tomato leaf discs followed by the assessment of thrips reproductive performance. The setup is designed to maintain gene expression during the course of the assay, where GFP signal in the control treatment is used as a reporter of expression. The screen is conducted in a climate box under controlled settings. As a result, multiple genes can be screened for their effect on thrips reproductive performance in a single experiment and in a relatively small space, without the need for generating stable transgenic plants. The method also eliminates the need for a greenhouse equipped to accommodate the combination of A. tumefaciens-infiltrations and thrips infestations. It is not only flexible and convenient for screening genes encoding putative thrips effectors but also for plant resistance genes or effector-targets of host plants and can be adapted for other crop plants, or other herbivorous arthropods.